CLINICAL AND LABORATORY CHARACTERISTICS OF SEASONAL INFLUENZA WITHCOMPLICATIONS IN CHILDREN AT THE NGHE AN NORTHWEST REGIONAL GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describethe clinical and subclinical characteristics of seasonal influenza with complications in children at Nghe An Northwest regional General Hospital.Method: Retrospective descriptive study in children with seasonal influenza with complications at Nghe An Northwest regional General Hospital from January 1, 2024 to December 31, 2024.Results: Of the total 327 pediatric patients diagnosed with seasonal flu complications. The group of 5 years old was 67.2%. The male/female ratio is 1.15/1. Flu vaccination within 12 months was 17.7%. The rate of influenza A was 77.7%, influenza B was 22.3%, and co-infection of influenza A and B was 5.2%. The highest incidence rate in the year was in winter. Clinical symptoms of fever were 100%, cough and sneezing/runny nose were 99.7%, and digestive symptoms were 34.6%. The white blood cell counts increased (45.0%). Anemia (21.7%). CRP increased (36.7%). Chest X-ray showed diffuse opacity (54.4%) and increased pulmonary vascular density (30.9%). Complications of seasonal flu in children included pneumonia (60.9%); bronchitis (29.1%); otitis media (11.6%); laryngitis (11.3%); respiratory failure (4.8%); encephalitis (1.2%); myositis (0.9%); myocarditis (0.6%).Conclusion: Seasonal flu with complications is common in the under 5 age group, with clinical symptoms of fever, cough, sneezing, runny nose and complications such as pneumonia and bronchitis.
Keywords: Seasonal flu, complications, children.